PHOTOELECTROCHEMICAL SOLAR CELLS BASED ON DYE-SENSITIZATION OF NANOCRYSTALLINE TIO2 - Gebeyehu, Desta; Sariciftci, N. Serdar (Zede Journal of Ethiopian Engineers and Architects, 2023)
Dye-sensitized solar cells (DSCs) have attracted considerable interest as low-cost alternatives to conventional inorganic photovoltaic devices. With low-cost raw materials and relatively low-cost manufacturing technology and processes, deposited thin films have the potential to provide more than a 50 percent reduction in cost relative to traditional crystalline cell modules. Hence, we investigated the photoelectrochemical properties of mesoporous colloidal anatase films in connection ~·ith their potential application in liquid junction photovoltaic cells. A respectable light to electric energy conversion efficiency of about 9.5% in 9 mW/cm2 (- 1110 Sun) was obtained. Jn comparison (a lsc = 2.2 mA/cm1 and an V0c = 600 mV under a white light l7lumination of 9 m W!cm1 ), we obtained !Jc = 15 mA!cm' and V oc ~ 7 60 m Vat a light intensity of 85 mW/cm1 (direct Sun). We achieved extraordinary efficiency for the conversion of incident photons to converted electrons exceeding 80% within the wavelength range of the absorption band from RuL2(NCS)2: 2 TBA sensliizer.